Temporal variations of flux and altitude of sulfur dioxide emissions during volcanic eruptions: implications for long-range dispersal of volcanic clouds - Boichu, M.; Clarisse, L.; Péré, J.-C.; Herbin, H.; Goloub, P.; Thieuleux, F.; Ducos, F.; Clerbaux, C.; Tanré, D. (Atmospheric chemistry and physics, 2015)
Sulfur-rich degassing, which is mostly composed of sulfur dioxide (SO2), plays a major role in the overall impact of volcanism on the atmosphere and climate. The accurate assessment of this impact is currently hampered by the poor knowledge of volcanic SO2 emissions. Here, using an inversion procedure, we show how assimilating snapshots of the volcanic SO2 load derived from the Infrared Atmospheric Sounding Interferometer (IASI) allows for reconstructing both the flux and altitude of the SO2 emissions with an hourly resolution. For this purpose, the regional chemistry-transport model CHIMERE is used to describe the dispersion of SO2 when released in the atmosphere. As proof of concept, we study the 10 April 2011 eruption of the Etna volcano (Italy), which represents one of the few volcanoes instrumented on the ground for the continuous monitoring of SO2 degassing. We find that the SO2 flux time-series retrieved from satellite imagery using the inverse scheme is in agreement with ground observations during ash-poor phases of the eruption. However, large discrepancies are observed during the ash-rich paroxysmal phase as a result of enhanced plume opacity affecting ground-based ultraviolet (UV) spectroscopic retrievals. As a consequence, the SO2 emission rate derived from the ground is underestimated by almost one order of magnitude. Altitudes of the SO2 emissions predicted by the inverse scheme are validated against an RGB image of the Moderate Resolution Imaging Spectroradiometer (MODIS) capturing the near-source atmospheric pathways followed by Etna plumes, in combination with forward trajectories from the Hybrid Single Particle Lagrangian Integrated Trajectory (HYSPLIT) model. At a large distance from the source, modelled SO2 altitudes are compared with independent information on the volcanic cloud height. We find that the altitude predicted by the inverse scheme is in agreement with snapshots of the SO2 height retrieved from recent algorithms exploiting the high spectral resolution of IASI. The validity of the modelled SO2 altitude is further confirmed by the detection of a layer of particles at the same altitude by the spaceborne Cloud-Aerosol Lidar with Orthogonal Polarization (CALIOP). Analysis of CALIOP colour and depolarization ratios suggests that these particles consist of sulfate aerosols formed from precursory volcanic SO2. The reconstruction of emission altitude, through inversion procedures which assimilate volcanic SO2 column amounts, requires specific meteorological conditions, especially sufficient wind shear so that gas parcels emitted at different altitudes follow distinct trajectories. We consequently explore the possibility and limits of assimilating in inverse schemes infrared (IR) imagery of the volcanic SO2 cloud altitude which will render the inversion procedure independent of the wind shear prerequisite.